Exploration of 4D Printing and its Applications in the Biomedical Sciences - Rana, Anjali; Mittal, Arun; Vashist, Chetan; Rajput, Shivam; Sridhar, Sathvik Belagodu; Malviya, Rishabha (Current Pharmaceutical Design, 2025)
The potential for 3D printing to completely transform future advanced manufacturing systems has been widely acknowledged. Recent developments in 3D printing technology, particularly in the areas of materials, printers, and procedures, have the potential to revolutionize numerous industries and improve our quality of life on a worldwide scale. 4D printed structures evolve and display intelligent behavior based on specific stimulus-smart material interaction mechanisms and the right design of multi-material structures from mathematical modelling. Time, printer, and shape/property/functionality evolution are the goals of 4D printing, which differs from 3D printing in that it is predictable and not dependent on any one factor. These features enable the product to be self-assembled, multi-functional, and self-repairing. The idea behind four-dimensional printing is the creation of sophisticated three-dimensional structures that can change form in response to various external stimuli. The article provides a comprehensive overview of the smart materials, activation mechanisms, and shape-changing processes used in 4D printing. 4D printing items can be engineered for diverse biomedical purposes, including cell scaffolds, vascular stents, bone scaffolds, tracheal stents, and cardiac stents, through various 3D printing methodologies, influenced by diverse challenges. Additionally, the article explores the potential of shape-changing structures and their present uses in several scientific and biomedical areas.
Keywords: 3D printing